1997
DOI: 10.1046/j.1464-410x.1997.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

The performance characteristics of the bladder tumour antigen test

Abstract: Objective  To evaluate the specificity and sensitivity of the Bard bladder tumour antigen (BTA) (Bard Inc, Covington, USA) test. Patients and methods  The performance of the BTA test was assessed prospectively in 98 patients (30 women and 68 men, mean age 64 years, median 67, sd 14.8) undergoing cystoscopy for various indications. The urine of the patients was assessed using the BTA test, cytology, culture and a dipstick test for haematuria, and the results compared with those from cystoscopy as the ‘standard’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Two studies included cystoscopy with biopsy as the reference standard [46,47], one of which also used IVU [47]. Four studies evaluated the bladder tumour antigen (BTA) test; none of these reported the threshold that would define a positive test result [38,40,46,48]. Five studies evaluated nuclear matrix protein 22 (NMP22); one used a threshold of 10 units/mL [45], and the others used 12 units/mL [36,37,42,43].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies included cystoscopy with biopsy as the reference standard [46,47], one of which also used IVU [47]. Four studies evaluated the bladder tumour antigen (BTA) test; none of these reported the threshold that would define a positive test result [38,40,46,48]. Five studies evaluated nuclear matrix protein 22 (NMP22); one used a threshold of 10 units/mL [45], and the others used 12 units/mL [36,37,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies evaluated tumour markers for detecting malignancy, primarily of the bladder [36][37][38][39][40][41][42][43][44][45][46][47][48]. On the whole, these studies were poorly reported and/or were subject to numerous potential sources of bias.…”
Section: Tumour Markersmentioning
confidence: 99%
See 3 more Smart Citations